2020
DOI: 10.1093/gerona/glaa315
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Statistical Parametric Mapping Identifies Impaired Orthostatic Cerebrovascular and Cardiovascular Response in Frailty Index

Abstract: Background Orthostasis is a potent physiological stressor which adapts with age. The age-related accumulation of health deficits in multiple physiological systems may impair the physiological response to orthostasis and lead to negative health outcomes such as falls, depression, and cognitive decline. Research to date has focused on changes with orthostasis at prespecified intervals of time, without consideration for whole signal approaches. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Capturing a broader range of morbidities may have masked underlying differences in cardiovascular multimorbidity, which may ultimately be the driver of the observed BP differences. Last, our finding of impaired BP and HR recovery with multimorbidity agrees with previous studies investigating frailty indices, 5,13,[33][34][35] suggesting that our multimorbidity scale captures key frailty factors contributing toward peripheral circulation impairment, and is likely an appropriate surrogate for frailty in the context of falls and syncope patients. Furthermore, we have found the strongest associations during the recovery period (30 s), which encourages the use of newly developed definitions such as delayed BP recovery 1 over more classic definitions such as initial OH or classical OH.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Capturing a broader range of morbidities may have masked underlying differences in cardiovascular multimorbidity, which may ultimately be the driver of the observed BP differences. Last, our finding of impaired BP and HR recovery with multimorbidity agrees with previous studies investigating frailty indices, 5,13,[33][34][35] suggesting that our multimorbidity scale captures key frailty factors contributing toward peripheral circulation impairment, and is likely an appropriate surrogate for frailty in the context of falls and syncope patients. Furthermore, we have found the strongest associations during the recovery period (30 s), which encourages the use of newly developed definitions such as delayed BP recovery 1 over more classic definitions such as initial OH or classical OH.…”
Section: Discussionsupporting
confidence: 89%
“…In males, similar but weaker trends may support a similar hypothesis, but the alternative hypothesis may also apply. Maguire et al identified differences in TSI between males and females during the first 30 s after standing, 13 and Jedrzejczyk-Spaho et al found lower values of TSI during a HUT in females than in males in their cohort of patients with suspected syncope. 27 Interestingly, resting cerebral perfusion is known to be higher in healthy females, 36 with CA often preserved in this cohort.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Relevant trials have shown that there is no significant benefit from strict blood pressure control in the elderly and that aggressive blood pressure control should be avoided even more in debilitated patients. [41] Our study concluded that the worse the overall health status of the elderly, the greater the blood pressure variability. Therefore, geriatricians should regulate blood pressure in elderly frail patients not only by lowering excessive blood pressure, but also by using long-acting, combination drugs to reduce blood pressure variability, and new anti-hypertensive drugs with blood pressure stabilizing effects are urgently needed.…”
Section: Discussionmentioning
confidence: 84%
“…Crucially, central and peripheral vascular hemodynamic changes occur in response to ageing, and frailty is associated with impaired cerebral autoregulation. 41 Distinguishing pathological disease states from ''healthy'' ageing is paramount for the development of effective interventions. For example, age is negatively correlated with penumbral volume (but not core volume) in individuals undergoing CT perfusion in the hyperacute stroke setting.…”
Section: Frailty and Cerebrovascular Pathophysiologymentioning
confidence: 99%